Recent progress in single-molecule transistors: their designs, mechanisms and applications. Issue 7 (17th November 2021) - Fu, Huanyan; Zhu, Xin; Li, Peihui; Li, Mengmeng; Yang, Lan; Jia, Chuancheng; Guo, Xuefeng
Abstract : Single-molecule field-effect transistors (FETs) are the key building blocks of electronic circuits and a unique platform for studying physical mechanisms. Here, the designs, mechanisms and applications of single-molecule FETs are summarized. Abstract : Single-molecule field-effect transistors (FETs) are the key building blocks of future electronic circuits. At the same time, they are also a unique platform for studying physical mechanisms at the single-molecule level. How to construct single-molecule FETs and how to efficiently control the charge transfer characteristics of the devices are two core issues in the development of single-molecule FETs. In this review, we present the research progress in single-molecule FETs with solid or liquid gates. Strategies to design single-molecule FETs are emphasized, including the design of functional molecules, the construction of gate electrodes and the control of molecule–electrode interface coupling. These single-molecule FETs provide a basis for practical applications and the exploration of physical laws. Specifically, the physical mechanisms of single-molecule FETs, especially those related to interfacial coupling, are explained, such as the energy level shift, Coulomb blockade effect, Kondo effect and electron–phonon coupling. The applications of single-molecule FETs are summarized, including the regulation of quantum interference, spin, thermoelectric effect and superconductivity. Finally, the current opportunities and challenges in the field of single-molecule FETs are proposed, aiming to promote the future development of single-molecule electronics.